Protein carbonyl levels correlate with performance in elite field hockey players - Rosa-Lima, F. L.; Lannes, L.; Viana-Gomes, D.; Pierucci, A. P. T. R.; Salerno, V. P. (Applied Physiology, Nutrition, and Metabolism, 2015)
Excess and incorrectly selected exercise can degrade athletic performance from an imbalance in redox homeostasis and oxidative stress, but well-planned training and nutrition can improve antioxidant capacity. The aim of the study was to investigate how nutrient intake could influence oxidative stress and cell lesion biomarkers after 5 days of training followed by a game. Blood was collected from 10 athletes at the start of training (basal), after training (pre-game), and postgame. Their acceleration capacity also was measured pre- and postgame. Blood analysis showed an increase in lactate concentration postgame (13%) and total antioxidant capacity increased both pre-game (13.1%) and postgame (12.7%), all in comparison with basal levels. An oxidative stress marker, protein carbonyl (PC), increased 3-fold over the course of the game, which correlated with a decreased acceleration (r = 0.749). For biomarkers of tissue damage, creatine kinase and aspartate transaminase (AST) increased postgame by 150% and 75%, respectively. The AST variation had a high negative correlation with energy and carbohydrate consumption and a moderate correlation with lipid and vitamin C intake. Protein intake had a positive but moderate correlation with reduced glutathione. The observed correlations suggest that nutritional monitoring can improve exercise physiological homeostasis and that PC serves as a good biomarker for oxidative stress and performance loss.